(untitled) (Journal of Applied Learning and Teaching, 2019)
This study seeks to examine the educational goals, learning approach, and assessment preferences among part-time Master of Business Administration (MBA) and Master of Professional Accounting (MPA) students in Singapore. The quantitative study uses a questionnaire that employs a revised two-factor study process questionnaire (R-SPQ-2F) to identify students’ approach to learning, and the adapted Assessment Preference Inventory (API) to examine students’ preferences to different assessment types and tasks. The sample comprises 101 students (55 MBA and 46 MPA students) from various age groups, of which 57 are male students. The results of this study showed that educational goals relating to career advancement/enhancement and improved knowledge and skills were the key motivational factors that lead students to pursue postgraduate studies. When it comes to approaches to learning, students generally reported adopting a deep learning approach. This approach to learning was also evident in the assessment preference where they preferred assessments that required problem solving and application of materials learnt during the course. Among the five assessment types, respondents have a strong preference for individual assignments and showed least preference for exams. However, there was no significant difference in the preference for any of the assessment items/format among gender and age groups. The findings in this study can inform curriculum redesign for both programmes to suit the needs of existing students and also to increase their appeal to prospective students. The respondents’ views on their learning approach and assessment preferences allow instructors and module leaders to rethink the teaching pedagogy and current assessment structure that favour assignments in order to improve students’ learning experience.